Social Transfers, Labor Supply And Poverty Reduction : The Case of Albania - Dabalen, Andrew (The World Bank, 2008)
In 1993, in response to persistent unemployment, and rising poverty and social unrest, the government of Albania introduced an anti-poverty program, namely Ndihma Ekonomike; in 1995 it was extended to all poor households. This paper estimates the separate effects of participation in this income support program and the old-age pension program on objective and subjective measures of household poverty. The analysis uses the nationally representative Albanian Living Standards Measurement Surveys carried out in 2002 and 2005. Using propensity score matching methods, the paper finds that Ndihma Ekonomike households, particularly urban residents, have lower per capita consumption and are more likely to be discontented with their lives, financial situation, and consumption levels than their matched comparators. In contrast, households receiving pensions are not significantly different from their matched comparators in reference to the same set of outcomes. The paper finds that the negative impact of Ndihma Ekonomike participation on welfare is driven by a negative labor supply response among work-eligible individuals. This negative labor response is larger among women and urban residents. In contrast to Ndihma Ekonomike, the receipt of old-age pension income transfers does not significantly impact the labor supply of prime-age individuals living in pension households